THE IMPACT OF CYBERBULLYING BEHAVIOR ON SOCIAL MEDIA INSTAGRAM ON ASSIROJIYAH SAMPANG HIGH SCHOOL STUDENTS - Irmalatis Syarifah; Muzakki Muzakki; Ernasari Ernasari; Muhyatun Muhyatun (PT Altin Riset Publishing, 2024)
This research aims to determine the impact of cyberbullying experienced by teenagers on the social media Instagram. The method used is qualitative research with a descriptive study type. In the analysis process carried out, this research refers to theoretical studies as well as journal articles related to Cyberbullying. The results of the research show that cyberbullying experienced by teenagers, especially students at Assirojiyah Sampang High School, has a significant impact and influences several aspects of their lives starting from psychological, physical, and social aspects.